PENERAPAN METODOLOGI TOGAF ADM UNTUK ANALISIS DAN PENYUSUNAN RENCANA STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI DI CALL CENTER 112 KOTA PALANGKA RAYA - Angelina, Yulia (Jurnal Ilmiah Sistem Informasi, 2023)
The role of information technology has penetrated into various sectors of life. With information technology allows organizational data to be processed quickly and easily so that the presentation of the required reports can be obtained precisely, quickly and efficiently. This can also be applied to the Palangka Raya City Emergency Call Fast Service (Call Center 112). Call Center 112 is a service center in receiving complaints and providing emergency information under the auspices of the Palangka Raya City Fire and Rescue Service. Call Center 112 has not implemented an information system that can increase effectiveness and efficiency in service quality. Therefore, proper IS/IT strategic planning is needed to support organizational performance. This research uses  the TOGAF ADM method. The results of this research are in the form of technology proposals and information systems in the form of strategic planning blueprints to be applied by organizations